Preliminary examination of the efficacy and safety of a standardized chamomile extract for chronic primary insomnia: A randomized placebo-controlled pilot study - Sen Ananda; Wright Benjamin D; Zick Suzanna M; Arnedt J Todd (BMC, 2011)
Abstract Background Despite being the most commonly used herbal for sleep disorders, chamomile's (Matricaria recutita) efficacy and safety for treating chronic primary insomnia is unknown. We examined the preliminary efficacy and safety of chamomile for improving subjective sleep and daytime symptoms in patients with chronic insomnia. Methods We performed a randomized, double-blind, placebo-controlled pilot trial in 34 patients aged 18-65 years with DSM-IV primary insomnia for ≥ 6-months. Patients were randomized to 270 mg of chamomile twice daily or placebo for 28-days. The primary outcomes were sleep diary measures. Secondary outcomes included daytime symptoms, safety assessments, and effect size of these measures. Results There were no significant differences between groups in changes in sleep diary measures, including total sleep time (TST), sleep efficiency, sleep latency, wake after sleep onset (WASO), sleep quality, and number of awakenings. Chamomile did show modest advantage on daytime functioning, although these did not reach statistical significance. Effect sizes were generally small to moderate (Cohen's d ≤ 0.20 to < 0.60) with sleep latency, night time awakenings, and Fatigue Severity Scale (FSS), having moderate effect sizes in favor of chamomile. However, TST demonstrated a moderate effect size in favor of placebo. There were no differences in adverse events reported by the chamomile group compared to placebo. Conclusion Chamomile could provide modest benefits of daytime functioning and mixed benefits on sleep diary measures relative to placebo in adults with chronic primary insomnia. However, further studies in select insomnia patients would be needed to investigate these conclusions. Trial Registration ClinicalTrials.gov Identifier NCT01286324